Pre-School Enrollment : An Analysis by Immigrant Generation - Barry R. Chiswick; Noyna DebBurman (Institute for the Study of Labor (IZA), 2004)
There has been minimal research on the pre-school enrollment of immigrant children. Using 1990 U.S. Census data, this paper investigates pre-school enrollment of child immigrants, those who immigrated as children and the U.S.-born children of immigrants. The analysis is conducted using probit analysis. Pre-school enrollment is found to vary systematically with parental characteristics (income and education), immigrant generation, number of siblings, mother?s labor supply and country of origin. Among the foreign-born, differences in preschool enrollment are analyzed by country of origin. Among the U.S.-born children of immigrants pre-school enrollment is greatest among those with both parents foreign born.
Keywords: J13; J15; I21; 330; immigrants; children; school enrollment; pre-school; Allgemeinbildende Schule; Migranten; Bildungsverhalten; Vereinigte Staaten